The Impact of Social Media Influencers and Use of Nostalgia on Brand Love in Luxury Brands - Theajonmaya, Arjun (2024)
A Master of Business Administration (MBA) thesis by Arjun Theajonmaya entitled, “The Impact of Social Media Influencers and Use of Nostalgia on Brand Love in Luxury Brands”, submitted in December 2024. Thesis advisor is Dr. Mohammed Sajid Khan. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).